Menggali Esensi Teori Generatif Transformatif Dan Implementasinya Dalam Pembelajaran Bahasa Arab - Intan Dwi Safitri; Ahmad Zidqy Azmy Hilmani; M Yunus Abu Bakar (JURNAL ILMIAH NUSANTARA, 2024)
This article discusses the transformational-generative theory developed by Noam Chomsky and its application in Arabic language learning. This theory explains how humans have an innate ability to acquire language through the Language Acquisition Device (LAD). Language structure consists of two parts: deep structure and surface structure, which are connected through transformational rules. This study aims to integrate the transformational-generative theory into Arabic language learning, taking into account the unique characteristics of Arabic, such as the i'rab system, verbal sentences (jumlah fi'liyah), and nominal sentences (jumlah ismiyah). This theory aids in generating an unlimited number of sentences through a creative process. Although the theory has the advantage of separating linguistic knowledge from speaking skills, its drawback lies in neglecting clauses and assuming that language is an innate ability that requires minimal practice.